Immersive Technology in Smart Cities Augmented and Virtual Reality in IoT - Aurelia, Sagaya; Paiva, Sara.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents recent trends and enhancements in the convergence of immersive technology and smart cities. The authors discuss various domains such as medical education, construction, brain interface, interactive storytelling, edification, and journalism in relation to combining smart cities, IoT and immersive technologies. The book sets up a medium to promulgate insights and in depth understanding among experts in immersive technologies, IoT, HCI and associated establishments. The book also includes case studies, survey, models, algorithms, frameworks and implementations in storytelling, smart museum, medical education, journalism and more. Various practitioners, academicians and researchers in the domain contribute to the book. Discusses the convergence of immersive technologies and smart cities from a variety of perspectives; Includes how augmented reality, mixed, and virtual reality in smart cities can aid in disaster administration, urban arrangement, direction-finding, and edification; Presents the latest trends for all academicians, researchers, business professionals studying smart cities and related fields.
Chapter 1. Exploring Immersive Technology in Education for Smart Cities -- Chapter 2. Immersive Learning about IC-Engine using Augmented Reality -- Chapter 3. Location-based Mobile Augmented Reality Systems: A systematic review -- Chapter 4. An Innovative Natural Disaster Precautionary Methods Through Virtual Space -- Chapter 5. Internet of Things: Survey on immersive healthcare technologies -- Chapter 6. Implementation of an Intelligent Model based on Big Data and Decision Making using Fuzzy Logic Type-2 for the car assembly industry in an industrial estate in northern Mexico -- Chapter 7. Cloud Computing Model on Wireless Ad Hoc Network using Clustering Mechanism for Smart City Applications -- Chapter 8. Smart Cities New Paradigm Applications and Challenges -- Chapter 9. A Survey on IoT Applications in Smart Cities -- Chapter 10. Internet of Things: Security Issues and Challenges -- Chapter 11. IoT Based Water Quality and Quantity Monitoring System for Domestic Usage -- Chapter 12. Threat Modelling, Attack Surfaces in IoT.
Keywords: Telecommunication; User interfaces (Computer systems).; Human-computer interaction; Computational intelligence; Technological innovations; Communications Engineering, Networks; User Interfaces and Human Computer Interaction; Computational Intelligence; Innovation and Technology Management; Augmented reality; Internet of things; Smart cities; Virtual reality